MTHFD2 promotes ovarian cancer growth and metastasis via activation of the STAT3 signaling pathway - Qiutong Li; Fang Yang; Xiu Shi; Shimin Bian; Fangrong Shen; Yuhong Wu; Chenjie Zhu; Fengqing Fu; Juan Wang; Jinhua Zhou; Youguo Chen (FEBS Open Bio, 2021)
Methylenetetrahydrofolate dehydrogenase 2 (MTHFD2) is a bifunctional enzyme located in the mitochondria. MTHFD2 has been reported to be overexpressed in several malignant tumors and is implicated in cancer development. This study aimed to investigate the effect of MTHFD2 on ovarian cancer progression. The expression of MTHFD2 was detected by bioinformatic analysis, immunohistochemistry, RT‐qPCR (real‐time quantitative PCR analysis), and western blot analysis. The effects of MTHFD2 depletion on cell proliferation, migration, and invasion were determined through in vitro experiments. Cell cycle progression and apoptosis were accessed by flow cytometry. The related signaling pathway protein expression was determined by western blot analysis. We found that MTHFD2 is highly expressed in both ovarian cancer tissues and cell lines. MTHFD2 deletion suppressed cell proliferation and metastasis. Knockdown of MTHFD2 induces cell apoptosis and G2/M arrest, whereas the number of cells in S phase increased with MTHFD2 overexpression. Mechanically, our results indicate that an inhibitory effect of MTHFD2 knockdown may be mediated by the downregulation of cyclin B1/Cdc2 complex and the inhibitory effect on its activity. Additionally, MTHFD2 could regulate cell growth and aggressiveness via activation of STAT3 and the STAT3‐induced epithelial–mesenchymal transition signaling pathway. These findings indicate that MTHFD2 is overexpressed in ovarian cancer and regulates cell proliferation and metastasis, presenting an attractive therapeutic target.